Critical questions on nutrition of preterm infants - Fabio Mosca; Maria Lorella Giannì; Paola Roggero; Camilla Menis; Laura Morlacchi; Nadia Liotto; Beatrice Bracco (Hygeia Press di Corridori Marinella, 2017)
Infants born preterm represent a nutritional emergency that must be addressed immediately in order to avoid/limit the development of nutritional deficits that lead to postnatal growth retardation. When taking care of preterm infants from a nutritional point of view, it must be taken into consideration that promotion of growth is achieved by the accomplishment of their high nutritional needs, that become even more demanding with the occurrence of comorbidities. Identification of the factors that determine and/or affect nutrient requirements is therefore mandatory. A full understanding of the most appropriate biological setting that should be used for establishing preterm infants nutritional requirements is desirable. A deeper knowledge with regard to these points would allow for the provision of appropriate amount of specific essential nutrients, avoiding the under- or overexposure to certain nutrients, and for the individualization of nutritional care of preterm infants. The avoidance of early malnutrition is of major importance since adequate postnatal growth has been associated with improvement of later neurodevelopment outcome. Limitation of extrauterine growth restriction prevents the need for rapid catch-up growth after discharge which, in turns, has been linked to later adverse metabolic consequences. Increasing evidence has indicated that postnatal growth retardation is accompanied by a fat-free mass deficit, probably related to immature metabolic mechanisms, delayed amino acid administration and protein intakes lower than recommendations. The potential long-lasting effects of these body composition modifications on future health, both in terms of neurodevelopment outcome and metabolic risk, are still under investigation.